Roles of the mitochondrial replisome in mitochondrial DNA deletion formation - Oliveira, Marcos T. [UNESP]; Pontes, Carolina de Bovi; Ciesielski, Grzegorz L. (Soc Brasil Genetica, 2020)
Mitochondrial DNA (mtDNA) deletions are a common cause of human mitochondrial diseases. Mutations in the genes encoding components of the mitochondrial replisome, such as DNA polymerase gamma (Pol gamma) and the mtDNA helicase Twinkle, have been associated with the accumulation of such deletions and the development of pathological conditions in humans. Recently, we demonstrated that changes in the level of wild-type Twinkle promote mtDNA deletions, which implies that not only mutations in, but also dysregulation of the stoichiometry between the replisome components is potentially pathogenic. The mechanism(s) by which alterations to the replisome function generate mtDNA deletions is(are) currently under debate. It is commonly accepted that stalling of the replication fork at sites likely to form secondary structures precedes the deletion formation. The secondary structural elements can be bypassed by the replication-slippage mechanism. Otherwise, stalling of the replication fork can generate single- and double-strand breaks, which can be repaired through recombination leading to the elimination of segments between the recombination sites. Here, we discuss aberrances of the replisome in the context of the two debated outcomes, and suggest new mechanistic explanations based on replication restart and template switching that could account for all the deletion types reported for patients.
Keywords: Mitochondria; DNA replication; human diseases; Pol gamma; Twinkle